Evaluation of a tool to score donor vein suitability for blood donation. Issue 6 (5th July 2019) - Hirani, Rena; O'Donovan, Justine; Knight, Elizabeth; Bell, Barbara; Mondy, Phillip
Abstract : Background and Objectives: Phlebotomy is a central task for whole blood donation, yet there are no published standards regarding systematic donor vein assessment or the impact of vein quality on successful blood donation. Blood donation failures and related adverse events are highly predictive of donors not returning for future blood donation. A specific blood donation vein scoring tool was assessed to measure donor vein suitability for whole blood collection and investigate the correlation of the donor's veins with donation outcomes. Materials and Methods: The vein assessment tool consisted of three questions using a 5‐point Likert‐type scale to measure responses. Two phlebotomists performed blinded assessments of each donor's veins on each arm using the tool. The individual measures were then aggregated to provide a total vein score out of 12. Inter‐rater reliability of the vein score tool was assessed by calculating the intraclass correlation coefficient for absolute agreement. Results: Fifty‐seven phlebotomists across four fixed blood donation centres performed paired vein assessments on 553 blood donors. The intraclass correlation coefficient indicated moderate inter‐rater reliability was achieved. The median scores for viable donations were 10, for non‐viable donations were 6·5 and for failed phlebotomies were 4. Donation histories of donors with lower vein scores indicated lower success during blood donation. Conclusion: The vein score tool appears to be predictive of a successful donation outcome, however, since there was not a suitably high correlation between the scores of the two assessors, further refinement of the tool will be required prior to wider use.